2021
DOI: 10.3102/0034654321990721
|View full text |Cite
|
Sign up to set email alerts
|

Moving Beyond Peer Review of Teaching: A Conceptual Framework for Collegial Faculty Development

Abstract: Over the past decades, peer review of teaching has become commonplace at many universities around the world. Though research on the topic is expanding, much of the literature is composed of qualitative studies that offer relevant empirical findings but often have limited foundations in theory. Using a framework synthesis approach, we synthesize the empirical findings of 48 qualitative articles on peer review of teaching into a comprehensive conceptual framework drawing on sociocultural perspectives of learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 63 publications
2
20
0
1
Order By: Relevance
“…The research shows that teachers may consider this tool as a bureaucratic process (Shortland, 2004); they can also refer to the process as a part of annual teacher performance appraisal. According to Esterhazy et al (2021), the majority of practitioners underestimate the value of peer observation by treating it as a one-time event rather than linking it to a broader understanding. This evaluative method can be regarded as challenging practice as it requires reflecting critically, detecting the pros and cons of teaching, providing constructive feedback and accepting negative comments (Bell, 2005).…”
Section: Benefits Of Peer Observationmentioning
confidence: 99%
“…The research shows that teachers may consider this tool as a bureaucratic process (Shortland, 2004); they can also refer to the process as a part of annual teacher performance appraisal. According to Esterhazy et al (2021), the majority of practitioners underestimate the value of peer observation by treating it as a one-time event rather than linking it to a broader understanding. This evaluative method can be regarded as challenging practice as it requires reflecting critically, detecting the pros and cons of teaching, providing constructive feedback and accepting negative comments (Bell, 2005).…”
Section: Benefits Of Peer Observationmentioning
confidence: 99%
“…Peer review of teaching, which includes colleagues engaging in exploratory dialogue about teaching practices and analysing different areas of practice, has, in recent years, become more commonly used as a tool for structured peer development in institutional settings (Donnelly, 2007;Gosling, 2014). Esterhazy et al (2021) identify collegial faculty development as an umbrella concept, revolving around different elements of collegial work in higher education, where university teachers observe each other during teaching and use these observations to generate reflective discussions around collaborative development on their teaching practices. Previous research has identified several positive outcomes of peer review, including the discovery of new ways of talking about teaching, increased confidence and emerging self-efficacy, the development of teaching skills and stronger collegiality, as well as mitigating feelings of isolation (e.g., Bell & Cooper, 2013;Centra, 1993;de Lange & Wittek, 2018;Donnelly, 2007;Engin, 2016;Hendry, Bell, & Thomson, 2014;Hutchings, 1996;Hutchings, 1995;Sell & Chism, 1988;Shortland, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, research on peer review also acknowledges some drawbacks (Gosling, 2014) regarding the subjective nature of what constitutes good teaching. For example, Esterhazy et al (2021) suggest that a teaching review process in which faculty are merely informed about how they are rated on various quality criteria rather than receiving formative feedback is less likely to contribute to the development of teaching quality. Other drawbacks include staff reluctance to engage in peer review and the risk of engaging in peer review only to comply with institutional policies, focusing too much on what is visible in the classroom, and the underlying power dynamic in the feedback situation, which might cause observed-teacher anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, by improving the quality of teaching, teachers come to the aid of students. This collaboration can lead to higher student motivation, but also to positive influences on learning outcomes (Esterhazy et al, 2021).…”
Section: Introductionmentioning
confidence: 99%